A multi‐module microfluidic platform for continuous pre‐concentration of water‐soluble ions and separation of oil droplets from oil‐in‐water (O/W) emulsions using a DC‐biased AC electrokinetic technique. Issue 5 (13th January 2017) - Das, Dhiman; Phan, Dinh‐Tuan; Zhao, Yugang; Kang, Yuejun; Chan, Vincent; Yang, Chun
Abstract : A novel continuous flow microfluidic platform specifically designed for environmental monitoring of O/W emulsions during an aftermath of oil spills is reported herein. Ionized polycyclic aromatic hydrocarbons which are toxic are readily released from crude oil to the surrounding water phase through the smaller oil droplets with enhanced surface area. Hence, a multi‐module microfluidic device is fabricated to form ion enrichment zones in the water phase of O/W emulsions for the ease of detection and to separate micron‐sized oil droplets from the O/W emulsions. Fluorescein ions in the water phase are used to simulate the presence of these toxic ions in the O/W emulsion. A DC‐biased AC electric field is employed in both modules. In the first module, a nanoporous Nafion membrane is used for activating the concentration polarization effect on the fluorescein ions, resulting in the formation of stable ion enrichment zones in the water phase of the emulsion. A 35.6% amplification of the fluorescent signal is achieved in the ion enrichment zone; corresponding to 100% enrichment of the fluorescent dye concentration. In this module, the main inlet is split into two channels by using a Y‐junction so that there are two outlets for the oil droplets. The second module located downstream of the first module consists of two oil droplet entrapment zones at two outlets. By switching on the appropriate electrodes, either one of the two oil droplet entrapment zones can be activated and the droplets can be blocked in the corresponding outlet.